Integrated management of Phytophthora seedling blight of safflower by seed treatment - and V.M. AMRUTSAGAR, D.R. MURUMKAR*, D.V. INDI, S.K. SHINDE (Indian Phytopathology, 2016)
A field experiment was conducted for three consecutive years to study the efficacy of chemicals and biological agents’ as a seed treatment for effective and economical management of Phytophthora seedling blight of safflower. Among different seed treatments, Cymoxanil 8% + Mancozeb 64% @ 0.2% was found to be the most significantly effective as it recorded least incidence of Phytophthora seedling blight (12.04%). It was followed by Trichoderma harzianum Th4d SC @ 2 ml/kg seed (19.27 %) and T. harzianum Th4d SC @ 1 ml/kg seed (20.16%) which were statistically indistinguishable. The data on seed yield and economics of safflower as influenced by different treatments indicated that seed treatment with Cymoxanil 8% + Mancozeb 64% @ 0.2% recorded significantly highest seed yield (904 kg/ha) and Benefit : Cost ratio of 2.06. It was followed by T. harzianum Th4d SC @ 1ml/kg seed (707 kg/ha, 1.59) and Captan 50% WP @ 0.3% (701 kg/ha, 1.61). The overall results indicated that for effective and economical management of Phytophthora seedling blight of safflower, it is recommended to treat the safflower seed before sowing with Cymoxanil 8% + Mancozeb 64% @ 2 g/kg or Captan 50% WP @ 3 g/kg or Trichoderma harzianum Th4d SC @ 1ml/kg seed.